PENGGUNAAN LABORATORIUM VIRTUAL PADA PEMBELAJARAN BIOLOGI DI SMA KOTA BANDA ACEH - Zainal Abidin Suarja (Bionatural : Jurnal Ilmiah Pendidikan Biologi, 2019)
With advances in information and communication technology, education and methods learning becomes easy and attractive for development. Now, ICT-based learning has begun to be used in the learning process both as a medium for conveying material to developments ICT-based laboratory. Besides as a means to facilitate service for learners, utilizing a virtual laboratory in the process learning is expected to be one of the solutions to solve learning problems experienced by learners in doing practical science so as to obtain a satisfactory learning outcomes. Long-term goals in this study is the emergence of proper application and suitable method to be used as a virtual laboratory in biology at the level of learning high school and university education. Specific targets to be achieved is The use of virtual labs in educational institutions as an alternative even the first choice in helping the learning process that will held, the election of some of the applications that can be used as a substitute a real laboratory, availability of guidebooks and modules to operate the application. The method to be used is a combination of quantitative and qualitative details of the survey and tests that will be tested by t-test and correlation as well as interviews, observation and study of the documentation that will be tested by the reduction, display and data verification. Plan activities began with a study literature and field studies to check and get the right information related virtual laboratory applications and reality on the ground, after which the team Researchers will inventory the applications that already exist, then identified in accordance with the level and the development of biological sciences. Furthermore, the research team will analyze with the help of expert groups Related applications that have been found by the research team, also do a comparison test against the application. Once validated, applications will be tested by the laboratory staff, teachers and lecturers as well as students and student. research shows that the virtual lab based learning can enhance students' mastery of concepts in biology learning, virtual learning lab methods can be used as an alternative to overcome the limitations of the lab equipment and the students responded well to the virtual lab-based learning. Keywords: laboratorium, virtual, pembelajaran biologi, SMA